find the zeros of the polynomial x square - 3 and verify the relationship between the zeros and the coefficients
Answers
Answered by
66
VickyskYy:
Nice
Answered by
85
Here is your solution
![\bold{\purple{\boxed{\boxed{\underline{Given:-}}}}} \bold{\purple{\boxed{\boxed{\underline{Given:-}}}}}](https://tex.z-dn.net/?f=%5Cbold%7B%5Cpurple%7B%5Cboxed%7B%5Cboxed%7B%5Cunderline%7BGiven%3A-%7D%7D%7D%7D%7D+)
![x {}^{2} - 3 = 0 \\ x {}^{2} = 3 \\ x = + - \sqrt{3} x {}^{2} - 3 = 0 \\ x {}^{2} = 3 \\ x = + - \sqrt{3}](https://tex.z-dn.net/?f=x+%7B%7D%5E%7B2%7D+-+3+%3D+0+%5C%5C+x+%7B%7D%5E%7B2%7D+%3D+3+%5C%5C+x+%3D+%2B+-+%5Csqrt%7B3%7D+)
![Zeroes\: are:- \\\:α = \sqrt{3} \: and \: β = - \sqrt{3} Zeroes\: are:- \\\:α = \sqrt{3} \: and \: β = - \sqrt{3}](https://tex.z-dn.net/?f=Zeroes%5C%3A+are%3A-+%5C%5C%5C%3A%CE%B1+%3D+%5Csqrt%7B3%7D+%5C%3A+and+%5C%3A+%CE%B2+%3D+-+%5Csqrt%7B3%7D+)
![\\<br />Coefficient \: are \\ <br /><br />a= 1 \\ <br />b= 0 \\ <br />c= -3 \\ <br /><br />Now \: relationship \: between \: the \: zeros \: and \: the \\ coefficients.\\ \\ 1.sum \: of \: zeroes \\ α+β= \frac{ - b}{a} \\ \\ \sqrt{3} + ( - \sqrt{ 3} ) = \frac{ - (0)}{1} \\ \\ 0 = 0 \\ \\<br />Coefficient \: are \\ <br /><br />a= 1 \\ <br />b= 0 \\ <br />c= -3 \\ <br /><br />Now \: relationship \: between \: the \: zeros \: and \: the \\ coefficients.\\ \\ 1.sum \: of \: zeroes \\ α+β= \frac{ - b}{a} \\ \\ \sqrt{3} + ( - \sqrt{ 3} ) = \frac{ - (0)}{1} \\ \\ 0 = 0 \\](https://tex.z-dn.net/?f=%5C%5C%3Cbr+%2F%3ECoefficient+%5C%3A+are+%5C%5C+%3Cbr+%2F%3E%3Cbr+%2F%3Ea%3D+1+%5C%5C+%3Cbr+%2F%3Eb%3D+0+%5C%5C+%3Cbr+%2F%3Ec%3D+-3+%5C%5C+%3Cbr+%2F%3E%3Cbr+%2F%3ENow+%5C%3A+relationship+%5C%3A+between+%5C%3A+the+%5C%3A+zeros+%5C%3A+and+%5C%3A+the+%5C%5C+coefficients.%5C%5C+%5C%5C+1.sum+%5C%3A+of+%5C%3A+zeroes+%5C%5C+%CE%B1%2B%CE%B2%3D+%5Cfrac%7B+-+b%7D%7Ba%7D+%5C%5C+%5C%5C+%5Csqrt%7B3%7D+%2B+%28+-+%5Csqrt%7B+3%7D+%29+%3D+%5Cfrac%7B+-+%280%29%7D%7B1%7D+%5C%5C+%5C%5C+0+%3D+0+%5C%5C+)
![2.product \: of \: zeroes \\ α× \: β = \frac{c}{a} \\ \\ \sqrt{3} \times - \sqrt{3} = \frac{ - 3}{1} \\ - 3 = -3 2.product \: of \: zeroes \\ α× \: β = \frac{c}{a} \\ \\ \sqrt{3} \times - \sqrt{3} = \frac{ - 3}{1} \\ - 3 = -3](https://tex.z-dn.net/?f=2.product+%5C%3A+of+%5C%3A+zeroes+%5C%5C+%CE%B1%C3%97+%5C%3A+%CE%B2+%3D+%5Cfrac%7Bc%7D%7Ba%7D+%5C%5C+%5C%5C+%5Csqrt%7B3%7D+%5Ctimes+-+%5Csqrt%7B3%7D+%3D+%5Cfrac%7B+-+3%7D%7B1%7D+%5C%5C+-+3+%3D+-3)
Similar questions
Social Sciences,
8 months ago
Social Sciences,
8 months ago
Physics,
1 year ago
Computer Science,
1 year ago
Math,
1 year ago